2015
DOI: 10.3917/spub.150.0199
|View full text |Cite
|
Sign up to set email alerts
|

Prise en charge intégrée des maladies mentales : l’exemple d’ Intermountain Healthcare (USA)

Abstract: Contexte : Parmi les maladies chroniques, la santé mentale est une priorité de santé publique en France et aux États-Unis. Si des progrès sont possibles en France, l’expérience d’ Intermountain Healthcare (IH), Utah, aux États-Unis, peut être source d’expérimentations probantes. Objectif : Identifier les enseignements de l’intégration clinique des spécialistes en santé mentale avec la médecine de ville de soins primaires, appelé Mental Health Integration (MHI) qui pourraient être utiles en France. Méthodes : C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(27 citation statements)
references
References 16 publications
0
27
0
Order By: Relevance
“…76 A narrative case study of mental health integration in a CCM showed that this co-support across disciplinary boundaries helps members of each profession not to feel alone in the face of complex multimorbidity issues about which they are not specialists and to make shared decisions on complex problems. 66 …”
Section: Causal Link 3:7 -Co-support and Decision-makingmentioning
confidence: 99%
See 4 more Smart Citations
“…76 A narrative case study of mental health integration in a CCM showed that this co-support across disciplinary boundaries helps members of each profession not to feel alone in the face of complex multimorbidity issues about which they are not specialists and to make shared decisions on complex problems. 66 …”
Section: Causal Link 3:7 -Co-support and Decision-makingmentioning
confidence: 99%
“…The support elaborated good practice recommendations and the corresponding indicators, which providers followed and measured. 66 In establishing PCMH, one problem for managers, as for researchers and other interventions too, was that different organisations varied considerably in their definitions of a PCMH, so in practice they were not all trying to implement the same intervention. 67 Some health systems have pursued the functions for which MCPs were designed through organisational integration, that is, amalgamating the separate components of primary care (i.e.…”
Section: Chaptermentioning
confidence: 99%
See 3 more Smart Citations